POLA MAKAN DAN STATUS GIZI BALITA DI DAERAH ALIRAN SUNGAI (DAS) DAN DAERAH TRANDAS DI WILAYAH KERJA PUSKESMAS SINGKIL - Misdar Aini; Evawany Y Aritonang; Fitri Ardiani (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
To obtain an optimal growth, the under five years old need the adequate, nutritious and balanced amount of food. The research was to find out the food pattern and nutritional status of under five years old in the watershed and trandas areas in the working area of Singkil health center. This purpose of this descriptive study with cross-sectional design. Total population of the study is 599 under five years old and the sample are 100 under five years old. The results of this study showed that most of the food patterns of under five years old was three times a day, the main food consumed by under five years old in the watershed and trandas was rice amounted 100,0%, the side dish most frequently consumed was fish 92,5% in the watershed and 92,7% in trandas, the vegetables mostly consumed in the watershed was kale 17,5% and in trandas was spinach 15,0%, and only small numbers of the under five years old consumed fruits, namely banana 10,0% in the watershed and 13,3% in trandas. The food pattern of under five years old the medium category, the level of energy consumption was 72,5% in the watershed and 75,0% in trandas, while the level of protein consumption was 65,0% in the watershed and 80,0% in trandas. Based on the index (weight/height) most of the nutritional status of under five years old was in normal category 87,5% in the watershed and 91,7% in trandas. Keywords: food pattern, nutritional status, under five years old, in the watershed and Trandas